An investigation of the (in)flexibility of the minibus-taxi operating license system: the case of Stellenbosch - Bergstedt, Roscoe (Department of Civil Engineering, 2023)
This research aims to explore the inflexibility of South Africa's operating licensing system and how it affects minibus taxis operations when operating locations change. It also explores the limitations it places on passenger demands when land uses change over time. The study focusses on answering the following research questions: How did the relocation of the rank effect passenger transit conditions? Why did the locations of the ranks change? Is the existing licensing system inflexible? Why were the operating license routes never amended? How did the outdated route description affect postrelocation traffic law enforcement conflict? It also explores what prompted decision-makers at the time to switch from an area-based permit to a route-based operating license by looking at legislative history and attempting to determine how this has influenced the taxi industry's operational dynamics. The Stellenbosch Municipality's efforts to modernize the town's public transportation network by simplifying and integrating all ranking facilities is investigated, but the effort is complicated by an operational licensing system that assigns permits to precisely specified routes. As a result of the reorganization of ranks, routes have become obsolete, resulting in violations of operational conditions in order to meet passenger demands while also creating law enforcement confrontation. Six of the Stellenbosch taxi association's ten routes were chosen for investigation. In addition to the literature review, 25 interviews were conducted with the intent of gaining a more in-depth understanding of respondents' attitudes and knowledge of the difficulties surrounding rank rationalization and consolidation. The data was gathered using a mixed method approach, with a qualitative study concentrating on the people affected by the system and a quantitative analysis focusing on the obsolete route descriptions. Taxi drivers, passengers, taxi owners, and municipal officials were interviewed and both open-ended and closed-ended questions formed part of the interview process. The purpose of the route surveying was to see how much the taxis deviate from the initial route description. This is descriptive data displayed in a graphical style via route maps, which were obtained by onboard tracking utilizing smart phone technology and GPS equipment to compare taxi operations to the initial route description in the operating license. Some of the routes mapped were established more than 20 years ago, however while some of the route's elements are still in use, others have become obsolete as land uses have changed. The mapping data was downloaded and converted into a keyhole markup language (KML) track. The analytical results are presented to clearly show the important factors that influenced the research design, which addresses the six research questions. The change in rank has clearly had a negative influence on daily operations and a variety of other factors, in addition to the passengers' travel experience. I learned that studies were conducted that guided the decision on the relocation of the ranks and because routes are not changed even with the aim to improve public transportation, that those critical aspects of the system remain intact making the operating licensing system in Stellenbosch inflexible. I also discuss the ambiguity surrounding why the operating license route description has not changed, as well as what each stakeholder must do to ensure the procedure is completed and offer data to demonstrate the growth in conflict between traffic officers and minibus taxi drivers. Regulation has its limits, but if the right measures are taken, the operating system may improve. Understanding the needs of passengers is one of the most important parts of public transportation service in order to ensure the long-term success of the industry's routes. Understanding how operating conditions and behavior affect route demand is also critical, and this research is focused on that. As regulations have changed around the world, the operating license system has been altered to provide a more flexible structure that is suited for the intended purpose of the operations. This gives the operating license system information and aids in determining its flexibility. The final chapter conclude the research and presents the findings and recommendations. The objective of this study was to look into the inflexibility of the operating licensing system, specifically how accommodating it is when ranks move and how it affects passenger experience, law enforcement conflict, and route specification.